The Role of Sanggar Asy-Syauqi in Reinforcing the Religious Practices of Islamic Education Students - Satrisno, Hengki; Alfauzan Amin; Zubaedi; Hery Noer Aly; Nur Hidayat, Wildan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the role of Sanggar Asy-Syauqi in reinforcing the religious practices of Islamic Education students at UIN Fatmawati Sukarno Bengkulu. Using a descriptive qualitative approach, the research explores how structured religious programs, spiritual mentoring, Qur’an recitation circles, and communal worship activities contribute to shaping students’ worship discipline, religious understanding, and internalization of Islamic values. Data were collected through in-depth interviews, participant observation, and documentation analysis involving sanggar administrators, active student members, and faculty mentors. The findings indicate that participation in the sanggar promotes consistent worship routines, enhances comprehension of religious principles, and fosters spiritual motivation supported by a collaborative and value-driven community environment. Students report significant personal and spiritual transformation, particularly in terms of prayer consistency, Qur’anic engagement, ethical awareness, and confidence in their religious identity as future Islamic educators. The study highlights the importance of campus-based religious studios as effective platforms for holistic spiritual development and suggests the need for further comparative research across different Islamic higher education institutions